Survival and human papillomavirus in oropharynx cancer in TAX 324: a subset analysis from an international phase III trial - Posner, M. R. (Ann Oncol, 2011)
Background: The association between human papillomavirus (HPV) and overall survival (OS) in oropharynx cancer (OPC) was retrospectively examined in TAX 324, a phase III trial of sequential therapy for locally advanced head and neck cancer. Methods: Accrual for TAX 324 was completed in 2003 and data updated through 2008. Pretherapy tumor biopsies were studied by PCR for human papillomavirus type 16 and linked to OS, progression-free survival (PFS) and demographics. Results: Of 264 patients with OPC, 111 (42%) had evaluable biopsies; 56 (50%) were HPV+ and 55 (50%) were HPV−. HPV+ patients were significantly younger (54 versus 58 years, P = 0.02), had T1/T2 primary cancers (49% versus 20%, P = 0.001), and had a performance status of zero (77% versus 49%, P = 0.003). OS and PFS were better for HPV+ patients (OS, hazard ratio = 0.20, P < 0.0001). Local–regional failure was less in HPV+ patients (13% versus 42%, P = 0.0006); at 5 years, 82% of HPV+ patients were alive compared with 35% of HPV− patients (P < 0.0001). Conclusions: HPV+ OPC has a different biology compared with HPV− OPC; 5-year OS, PFS, and local–regional control are unprecedented. These results support the possibility of selectively reducing therapy and long-term morbidity in HPV+ OPC while preserving survival and approaching HPV− disease with more aggressive treatment.